-4x(-x)=

Simple and best practice solution for -4x(-x)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x(-x)= equation:


Simplifying
-4x(-1x) = 0

Remove parenthesis around (-1x)
-4x * -1x = 0

Reorder the terms for easier multiplication:
-4 * -1x * x = 0

Multiply -4 * -1
4x * x = 0

Multiply x * x
4x2 = 0

Solving
4x2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '4'.
x2 = 0

Simplifying
x2 = 0

Take the square root of each side:
x = {0}

See similar equations:

| 10d+4=7d+16 | | 4(m+2)= | | 6y^2-y-12=0 | | x+8=2(x+24) | | 6(a+3)-15= | | 4(m-2)+2(3m+2)= | | 8x-16=4x-4 | | 525+0.21x=850 | | 11x+5=4x+9 | | x+6=40 | | 13(4x-7)=13 | | 8(3x+6)=96 | | 2(x+7)=56 | | s^2+s+4=0 | | 71-6x=35 | | 22+4x=50 | | y^2-4= | | 5x-73=27 | | 2Y^3-Y+3X-2=0 | | 6x+29=13x+41 | | s^2-s+4=0 | | (6x-7)+9x=68 | | 10x-117=5x-7 | | 8x^7y(5x^6y^2-6x^2+4y^3)= | | 5(2y+4)= | | -2+3(x-9)-2(x+3)=0 | | 2z^2+40=-8z | | 4+x=117 | | p+4p=60 | | 5x^2+30x-10=0 | | 3n+5=n-8 | | 3y(2y-4)=16 |

Equations solver categories